Primerjalnopravna analiza kazenske odgovornosti bankirjev za slabe kredite - Kvas, Nastja (Podjetje in delo, 2016)
Slovenian banks broke their own internal regulations as well as legal regulations when granting credits. Loans were being approved although it was known that borrower's balance sheet and insurance were not appropriate and the credit documentation was inadequate, risk managers' opinions were not taken into account, etc. Other countries in the world as well are facing problems with bad credit approvals. The purpose of this article is to emphasize critical weaknesses in Slovenian legal regulations and introduce possible solutions by analysing foreign legal orders.
Keywords: bančništvo; banke; kazenska odgovornost; krediti; kreditiranje; odgovornost; poslovno tveganje; zavarovanje